Ética pública & buen gobierno = Public ethics & good government. - Manjarrez, J. (Universidad Autónoma de Nuevo León, 2007)
Abstract. Modern societies demand governments promoting equitable and sustainable development and combating corruption. In the different areas of the public administration, factors such as transparency, efficiency, effectiveness, accountability, economy, human rights and respect to the legal framework are of great relevance for a good government. In Mexico it is necessary to reinforce the ethical aspect in the public administration to diminish the level of corruption. The ethical behavior of the public servant is related to integrity, honesty, transparency, expertise and leadership, it is part of the social capital of a country and a necessary condition to a good government and to eradicate corruption. It is essential to establish efficient systems, programs and mechanisms to promote the importance of ethics in government and society. Finally, society must vote to punish or reward the government performance, recognize its social duties and rights, demand the equal exercise of the law and always act ethically.